Implementasi Metode RAD Pada Sistem Informasi Wedding Organizer Berbasis Website - Ali Haidir (Universitas Mohammad Husni Thamrin, 2021)
Web-based wedding organizer information systems nowadays are very much needed, especially for wedding packages service that can make it easier for customers to choose the packages provided as well as ordering without having to go to the place or location where the wedding organizer is located. This convenience can be obtained by building an information system that can accommodate the needs of customers, the needs of the sales department, the administration of the wedding organizer company to facilitate the preparation of reports to be submitted to the wedding organizer owner. In addition, the computerized data processing system will speed up the process of selecting services such as; wedding package, order, purchase and reports. In developing this system, two sides are needed where visitors will become customers and the website administrator will manage the website. The system development method used in this system design uses the Rapid Application Development (RAD) method. The results showed that by building a computerized system that is assisted by using the PHP programming language, more data are stored and reports can be presented real time.